Antiviral coating composition, coating film, and article

By using metal-doped silica, vinyl pyrrolidone units and alcohol-based solvents in the coating composition, combined with ball milling treatment technology, a coating film that maintains excellent antiviral performance on the surface of the article for a long time is solved, and antiviral in the prior art is solved The problem of difficulty in maintaining performance for a long time is especially insufficient resistance to non-encapsulated viruses.

CN119173592APending Publication Date: 2024-12-20TOYO SEIKAN GRP HLDG LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202380039933.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-08
Filing Date
2023-06-06
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Existing antiviral coatings are difficult to maintain excellent antiviral properties on the surface of the article for a long time, especially inadequate resistance to non-encapsulated viruses.

Method used

The coating composition using a coating composition containing a polymer containing metal-doped silica, vinyl pyrrolidone units and an alcohol-based solvent or a mixed solvent of an alcohol-based solvent and water is uniformly dispersed by ball milling technology to form a solid coating.

Benefits of technology

It has achieved excellent antiviral performance in metal-doped silica on the surface of the article for a long time, and has shown strong antiviral effects on both enveloped viruses and non-encapsulated viruses, enhancing the antiviral protection ability of the article.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119173592A_ABST
    Figure CN119173592A_ABST
Patent Text Reader

Abstract

The present invention addresses the problem of providing: an antiviral coating composition which is capable of forming a coating film that exhibits excellent antiviral properties in metal-doped silica and can be firmly held on the surface of an article; a coating film formed from the antiviral coating composition; and an article having the coating film. The antiviral coating composition according to the present invention, as a solution, contains (1) a metal-doped silica; (2) a polymer containing a vinyl pyrrolidone unit; and (3) an alcohol-based solvent or a mixed solvent of an alcohol-based solvent and water. The coating film of the present invention is formed from the antiviral coating composition of the present invention. The article of the present invention has the coating film of the present invention.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an antiviral coating composition, a coating film and an article. Background Art

[0002] As is known to all, in recent years, since the emergence of new influenza viruses and coronaviruses that cause severe symptoms due to infection, people have become increasingly concerned about antiviral preparations for viral infection countermeasures. According to the structure, viruses can be roughly divided into viruses with an envelope composed of lipids or glycoproteins (enveloped viruses) and viruses without an envelope (non-enveloped viruses). Influenza virus is a representative example of enveloped viruses, and norovirus is a representative example of non-enveloped viruses. Compared with enveloped viruses, non-enveloped viruses can be said to have stronger resistance to alcohol and heat, etc., and are more contagious. Therefore, people have invested a lot of energy in the research and development of antiviral preparations that not only show excellent antiviral effects on enveloped viruses, but also on non-enveloped viruses. Regarding this type of antiviral preparation that shows excellent antiviral effects not only on enveloped viruses but also on non-enveloped viruses, the inventors of the present invention and others have also proposed a metal-doped silica inorganic antiviral preparation in patent document 1.

[0003] The inorganic antiviral preparation proposed by the inventors in Patent Document 1 can be used as a material to impart antiviral properties to various objects around us. As a method of utilizing it, when metal-doped silica is combined with a coating composition and applied to the surface of an object, the coating film formed by the coating composition containing metal-doped silica needs to make the metal-doped silica exhibit excellent antiviral properties and also needs to be firmly maintained on the surface of the object.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2021-175741 Summary of the invention

[0007] Problems to be solved by the invention

[0008] Therefore, the object of the present invention is to provide an antiviral coating composition that can form a coating film in which metal-doped silica exhibits excellent antiviral properties and is firmly maintained on the surface of an article, a coating film formed by the antiviral coating composition, and an article having the coating film.

[0009] Technical solutions to solve problems

[0010] In view of the above aspects, the inventors conducted in-depth research and found that in the process of manufacturing a coating composition containing metal-doped silica, when a polymer containing vinyl pyrrolidone units is used as a resin component (film-forming agent), the coating film formed by the coating composition is a product in which the metal-doped silica exhibits excellent antiviral properties and is firmly maintained on the surface of the article.

[0011] The antiviral coating composition of the present invention completed based on the above cognition is as described in claim 1, comprising

[0012] (1) Metal-doped silica;

[0013] (2) polymers containing vinyl pyrrolidone units; and

[0014] (3) An alcohol solvent or a mixed solvent of an alcohol solvent and water.

[0015] In addition, the antiviral coating composition described in claim 2 is the antiviral coating composition described in claim 1, wherein the metal doped into the silica is selected from at least one of copper, aluminum, zirconium, cobalt, manganese, and iron.

[0016] In addition, the antiviral coating composition described in claim 3 is the antiviral coating composition described in claim 2, wherein the metal doped into the silica is copper and / or aluminum.

[0017] In addition, the antiviral coating composition described in claim 4 is the antiviral coating composition according to claim 1, wherein the silica is porous silica.

[0018] In addition, the antiviral coating composition described in claim 5 is the antiviral coating composition described in claim 1, wherein the polymer containing the pyrrolidone unit is a copolymer of a vinyl pyrrolidone unit and a unit other than vinyl pyrrolidone.

[0019] In addition, the antiviral coating composition described in claim 6 is the antiviral coating composition described in claim 5, wherein the ratio of the vinyl pyrrolidone unit to the unit other than vinyl pyrrolidone (vinyl pyrrolidone unit: unit other than vinyl pyrrolidone) is 2:8 to 8:2.

[0020] In addition, the antiviral coating composition according to claim 7 is the antiviral coating composition according to claim 5, wherein the copolymer of the vinyl pyrrolidone unit and the unit other than vinyl pyrrolidone is a copolymer of vinyl pyrrolidone and vinyl acetate.

[0021] In addition, the antiviral coating composition according to claim 8 is the antiviral coating composition according to claim 1, wherein the polymer containing a pyrrolidone unit is polyvinylpyrrolidone.

[0022] Furthermore, the antiviral coating composition according to claim 9 is the antiviral coating composition according to claim 1, wherein the weight average molecular weight of the polymer containing the pyrrolidone unit is 5,000 to 1,500,000.

[0023] In addition, the antiviral coating composition according to claim 10 is the antiviral coating composition according to claim 1, wherein the alcohol solvent is ethanol.

[0024] In addition, the antiviral coating composition described in claim 11 is the antiviral coating composition described in claim 1, wherein the contents of metal-doped silica, polymer containing vinyl pyrrolidone units, alcohol solvent or a mixed solvent of alcohol solvent and water in the antiviral coating composition are respectively: the content of metal-doped silica is 0.1 to 20 weight %, the content of polymer containing vinyl pyrrolidone units is 0.1 to 20 weight %, and the content of alcohol solvent or a mixed solvent of alcohol solvent and water is 60 to 99.8 weight %.

[0025] In addition, the antiviral coating composition described in claim 12 is the antiviral coating composition described in claim 1, wherein the weight ratio of metal-doped silica to the polymer containing vinyl pyrrolidone units (metal-doped silica: polymer containing vinyl pyrrolidone units) is 1:99 to 75:25.

[0026] In addition, the method for producing the antiviral coating composition of the present invention is as described in claim 13, comprising the steps of placing the following (1) to (3) in a processing container and subjecting the mixture to ball milling treatment,

[0027] (1) Metal-doped silica;

[0028] (2) polymers containing vinyl pyrrolidone units; and

[0029] (3) An alcohol solvent or a mixed solvent of an alcohol solvent and water.

[0030] Furthermore, the antiviral coating film of the present invention comprises, as described in claim 14, (1) metal-doped silica and (2) a polymer containing a vinyl pyrrolidone unit.

[0031] Furthermore, the antiviral coating film according to claim 15 is the antiviral coating film according to claim 14 , wherein the antiviral coating film is formed from the antiviral coating composition according to claim 1 .

[0032] Furthermore, the article of the present invention, as recited in claim 16, comprises the antiviral coating film recited in claim 14.

[0033] Effects of the Invention

[0034] According to the present invention, there can be provided an antiviral coating composition in which metal-doped silica exhibits excellent antiviral performance and can be firmly maintained as a coating film on the surface of an article, a coating film formed by the antiviral coating composition, and an article having the coating film. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a micrograph of a coating film formed by the antiviral coating composition of the present invention produced in Production Example 11. DETAILED DESCRIPTION

[0036] The antiviral coating composition of the present invention comprises:

[0037] (1) Metal-doped silica;

[0038] (2) polymers containing vinyl pyrrolidone units; and

[0039] (3) An alcohol solvent or a mixed solvent of an alcohol solvent and water.

[0040] In the antiviral coating composition of the present invention, the metal-doped silica may be, for example, an inorganic antiviral preparation as described in Patent Document 1. Here, "metal-doped silica" refers to silica in which a metal is introduced by chemical bonding in an inorganic network formed by siloxane bonds constituting silica. The metal-doped silica may be porous or non-porous, and there is no particular limitation on its shape.

[0041] Examples of the metal to be doped into silicon dioxide include copper, aluminum, zirconium, cobalt, manganese, and iron. These metals may be used alone or in combination of two or more.

[0042] The metal content in the metal-doped silica (the total amount of each metal when two or more metals are used in combination) is, for example, 0.01 to 40% by weight, preferably 0.1 to 20% by weight, and more preferably 1 to 10% by weight. If the metal content in the metal-doped silica is less than 0.01% by weight, it may not be possible to obtain a sufficient antiviral effect. On the other hand, silica doped with more than 40% by weight of metal may be difficult to manufacture. When two or more metals are used in combination, the content ratio between the metals can be, for example, 0.1 to 2 times the content of one metal.

[0043] When the metal-doped silica is porous, the metal-doped porous silica may be, for example, a product described in Japanese Patent Application Laid-Open No. 2020-15640 by the present inventors. The details are as follows.

[0044] Examples of porous silica include mesoporous silica in which micropores (mesopores) having a diameter of 2 to 50 nm are regularly arranged.

[0045] The specific surface area of ​​porous silica is, for example, 500 to 2000 m 2 / g is preferred because durability can be maintained.

[0046] The metal-doped mesoporous silica can be produced by the following method which is known per se and is described in, for example, JP-A-2020-15640.

[0047] (Process 1)

[0048] First, a surfactant and a raw material for doping mesoporous silica with a metal are dissolved in a solvent, and micelles are formed in the surfactant by stirring at a temperature of, for example, 30 to 200° C. for 0.5 to 10 hours.

[0049] The amount of the surfactant dissolved in the solvent is, for example, 10 to 400 mmol / L, preferably 50 to 150 mmol / L. Alternatively, the amount of the surfactant dissolved in the solvent is, for example, 0.01 to 5.0 mol, preferably 0.05 to 1.0 mol, relative to 1 mol of the silica raw material added in step 2 described below.

[0050] As a surfactant, any one of a cationic surfactant, an anionic surfactant, and a nonionic surfactant can be used, preferably a cationic surfactant such as an alkyl ammonium salt. The alkyl ammonium salt is preferably an ammonium salt of an alkyl group with a carbon number of 8 or more, and considering the industrial availability, it is more preferably an ammonium salt of an alkyl group with a carbon number of 12 to 18. As a specific example of an alkyl ammonium salt, hexadecyl trimethyl ammonium chloride, cetyl trimethyl ammonium bromide, stearyl trimethyl ammonium bromide, cetyl trimethyl ammonium chloride, stearyl trimethyl ammonium chloride, dodecyl trimethyl ammonium bromide, octadecyl trimethyl ammonium bromide, dodecyl trimethyl ammonium chloride, octadecyl trimethyl ammonium chloride, didodecyl dimethyl ammonium bromide, ditetradecyl dimethyl ammonium bromide, didodecyl dimethyl ammonium chloride, and ditetradecyl dimethyl ammonium chloride can be cited. The surfactant can be used alone or in combination of two or more.

[0051] The amount of the raw materials used to dope the metal into the mesoporous silica dissolved in the solvent (the total amount of the raw materials when two or more metals are used in combination) is, for example, 0.001 to 1 mol, preferably 0.005 to 0.5 mol, and more preferably 0.01 to 0.1 mol, relative to 1 mol of the silica raw material added in the later-described step 2.

[0052] As raw materials for doping metals into mesoporous silica, for example, nitrates, sulfates, chlorides, and oxychlorides of metals can be used. When copper is doped, copper nitrate, copper chloride, and the like are preferably used. When aluminum is doped, aluminum chloride is preferably used. When zirconium is doped, zirconium oxychloride is preferably used. When cobalt is doped, cobalt nitrate is preferably used. When manganese is doped, manganese chloride is preferably used. When iron is doped, ferric chloride is preferably used. The raw materials for doping metals can be used alone or in combination of two or more.

[0053] As the solvent, for example, water can be used, or the solvent may be a mixed solvent of water and a water-soluble organic solvent represented by a polyol such as methanol, ethanol, diethylene glycol, and glycerin.

[0054] (Process 2)

[0055] Next, in the solution of the surfactant micelles obtained in step 1, a silica raw material is dissolved and stirred at room temperature, for example, until uniform, so that the silica raw material is aggregated on the micelle surface of the surfactant. The amount of silica raw material dissolved in the solution is, for example, 0.2 to 1.8 mol / L. Alternatively, when water or a mixed solvent of water and a water-soluble organic solvent is used as the solvent, it is, for example, 0.001 to 0.05 mol relative to 1 mol of water.

[0056] The silica raw material can be any material that can form an inorganic network composed of siloxane bonds constituting mesoporous silica through dehydration condensation, and there is no particular limitation. As a specific example of the silica raw material, tetraalkoxysilanes such as tetraethoxysilane, tetramethoxysilane, and tetra-n-butoxysilane and sodium silicate can be cited. Preferably, tetraalkoxysilane, more preferably tetraethoxysilane. The silica raw material can be used alone or in combination of two or more.

[0057] (Process 3)

[0058] Next, the silica raw material gathered on the surface of the surfactant micelle is dehydrated and condensed to form an inorganic network composed of siloxane bonds constituting mesoporous silica, and the metal is introduced into the inorganic network through chemical bonds. The dehydration and condensation of the silica raw material can be achieved by, for example, adding an alkaline aqueous solution to the system to increase the pH value and stirring at room temperature for more than 1 hour. The addition of the alkaline aqueous solution is preferably such that the pH value immediately changes to 8 to 14 after addition, and more preferably changes to 9 to 11. As specific examples of alkaline aqueous solutions, there can be cited aqueous sodium hydroxide solution, aqueous sodium carbonate solution, and ammonia water, preferably aqueous sodium hydroxide solution. The alkaline aqueous solution can be used alone or in combination of two or more. It should be noted that the dehydration and condensation of the silica raw material can also be achieved by adding an acidic aqueous solution such as an aqueous hydrochloric acid solution to the system to lower the pH value and then stirring.

[0059] (Process 4)

[0060] Finally, the micelles of surfactant formed on the surface of the inorganic network composed of siloxane bonds constituting mesoporous silica and metals introduced through chemical bonds obtained in step 3 are filtered and recovered as precipitates, dried at a temperature of, for example, 30 to 70° C. for 10 to 48 hours, and then calcined at a temperature of 400 to 600° C. for 1 to 10 hours to obtain the metal-doped mesoporous silica as the target product. The metal-doped mesoporous silica thus obtained can also be crushed to a desired particle size (for example, a median particle size of 0.01 to 100 μm) using a mixer, a grinder, etc. as needed.

[0061] It should be noted that the raw materials added into the system for doping metals into the mesoporous silica are not limited to the method of dissolving them in the solvent together with the surfactant in the above-mentioned step 1. It can be added before the step 3 in which the silica raw materials are dehydrated and condensed to form an inorganic network composed of siloxane bonds constituting the mesoporous silica. It can also be dissolved in the solution in step 2 or step 3.

[0062] In the case where the metal-doped silica is non-porous, the metal-doped non-porous silica can be manufactured using, for example, a sedimentation method which is a common method for manufacturing non-porous silica. Specifically, when the alkali metal silicate as a raw material for silica is neutralized with an inorganic acid, it can be manufactured by allowing the raw materials for doping the metal into the non-porous silica to coexist in the system. The raw materials for doping the metal into the non-porous silica can be the same as the raw materials for doping the above-mentioned metal into the mesoporous silica. Regarding the amount of the raw material for doping the metal into the non-porous silica (the total amount of each raw material when two or more metals are used in combination), relative to 1 mol of the alkali metal silicate as the raw material for silica, for example, 0.001 to 0.5 mol, preferably 0.01 to 0.1 mol. The alkali metal silicate used as a raw material for silica can be a conventional alkali metal silicate used for manufacturing non-porous silica by a sedimentation method. Specifically, sodium silicate, potassium silicate, etc. can be cited, and the molar ratio of silicon dioxide to alkali SiO2 / M2O (M is Na, K, etc.) is, for example, 0.5 to 4. The amount of alkali metal silicate dissolved in the solvent (water, etc.) is, for example, 0.001 to 0.05 mol relative to 1 mol of the solvent. As inorganic acids, hydrochloric acid, sulfuric acid, nitric acid, etc. can be used. Metal-doped non-porous silica can be obtained as a precipitate generated by the neutralization reaction of alkali metal silicate and inorganic acid, and its filtration, washing, drying, etc. can be carried out according to the method used when manufacturing non-porous silica by sedimentation method. If necessary, it can be finally sintered at a high temperature of more than 300°C. The specific surface area (BET specific surface area) of the metal-doped non-porous silica manufactured in this way is, for example, 0.1 to 350m 2 If necessary, the material may be pulverized by a mixer or a grinder to have a desired particle size (eg, a median particle size of 0.01 to 100 μm), similar to the above-mentioned metal-doped mesoporous silica.

[0063] In the antiviral coating composition of the present invention, the polymer containing vinyl pyrrolidone units used as a resin component may be, for example, a copolymer of vinyl pyrrolidone units and units other than vinyl pyrrolidone. In this case, in order to easily form a coating film that allows the metal-doped silica to exhibit excellent antiviral properties and is firmly maintained on the surface of the article, the ratio of the vinyl pyrrolidone unit to the unit other than vinyl pyrrolidone (vinyl pyrrolidone unit: unit other than vinyl pyrrolidone) is preferably 2:8 to 8:2. Specific examples of copolymers of vinyl pyrrolidone units and units other than vinyl pyrrolidone include copolymers of vinyl pyrrolidone and dimethylaminoethyl methacrylate, copolymers of vinyl pyrrolidone and methylvinyl imidazoline chloride, copolymers of vinyl pyrrolidone and dimethylaminopropionamide methacrylate, copolymers of vinyl pyrrolidone and quaternized imidazoline, copolymers of vinyl pyrrolidone and vinyl caprolactam and methylvinyl imidazolium methyl sulfate, copolymers of vinyl pyrrolidone and vinyl acetate, copolymers of vinyl pyrrolidone and eicosene, copolymers of vinyl pyrrolidone and hexadecene, copolymers of vinyl pyrrolidone and styrene, copolymers of vinyl pyrrolidone and vinyl caprolactam and dimethylaminoethyl methacrylate. In addition, the polymer containing the vinyl pyrrolidone unit may also be polyvinyl pyrrolidone. The weight average molecular weight of the polymer containing vinyl pyrrolidone units is, for example, 5,000 to 1,500,000, preferably 6,000 to 1,000,000, more preferably 7,000 to 500,000, and further preferably 8,000 to 100,000. When the weight average molecular weight of the polymer containing vinyl pyrrolidone units is too small, when the metal-doped silica is porous, the molecules will enter the micropores of the silica, and when it is expected that the performance brought by the micropores other than antiviral performance (such as deodorization, etc.) will be exhibited, it may be difficult to exhibit such performance; and when the weight average molecular weight is too large, the molecules will completely cover the surface of the silica, which may hinder the antiviral activity of the silica exhibited by adsorbing viruses. The polymer containing vinyl pyrrolidone units can be used alone or in combination of two or more.

[0064] In the antiviral coating composition of the present invention, the alcohol solvent may be a conventional solvent used as a component of the coating composition, and specific examples thereof include methanol, ethanol, and isopropanol. The alcohol solvent may be used alone or in combination of two or more. When a mixed solvent of an alcohol solvent and water is used, the weight ratio of the alcohol solvent to water (alcohol solvent: water) is, for example, 1:5 to 100:1.

[0065] In the antiviral coating composition of the present invention, the content of metal-doped silica, polymer containing vinyl pyrrolidone units, alcoholic solvent or mixed solvent of alcoholic solvent and water is, for example, 0.1 to 20% by weight of metal-doped silica, 0.1 to 20% by weight of polymer containing vinyl pyrrolidone units, and 60 to 99.8% by weight of alcoholic solvent or mixed solvent of alcoholic solvent and water. The antiviral coating composition of the present invention may contain pigments, fragrances, dispersants, defoamers, leveling agents, lubricants, mildewproof agents, preservatives, waxes, etc., which are commonly used as components of coating compositions. In the case of combining these components, the content of alcoholic solvent or mixed solvent of alcoholic solvent and water will reduce the content of these components accordingly. In addition, when manufacturing the antiviral coating composition of the present invention, when the metal-doped silica is provided in the form of a slurry suspended in a dispersion medium that is different from the alcohol solvent or a mixed solvent of an alcohol solvent and water used in the antiviral coating composition of the present invention, or when the polymer containing vinyl pyrrolidone units is provided in the form of a solution dissolved in a solvent that is different from the alcohol solvent or a mixed solvent of an alcohol solvent and water used in the antiviral coating composition of the present invention, the antiviral coating composition of the present invention may contain such a dispersion medium or solvent, in which case, the content of the alcohol solvent or the mixed solvent of an alcohol solvent and water will be reduced accordingly by the content of this part of the component.

[0066] The weight ratio of metal-doped silica to the polymer containing vinyl pyrrolidone units in the antiviral coating composition of the present invention (metal-doped silica: polymer containing vinyl pyrrolidone units) is preferably 1:99 to 75:25, more preferably 15:85 to 70:30, and further preferably 25:75 to 65:35. If the ratio of metal-doped silica is too low, it may be difficult to form a metal-doped silica coating film showing excellent antiviral performance; on the other hand, if the ratio of the polymer containing vinyl pyrrolidone units is too low, it may be difficult to form a coating film that is firmly maintained on the surface of the article.

[0067] The antiviral coating composition of the present invention can be prepared by mixing metal-doped silica, a polymer containing a vinyl pyrrolidone unit, an alcoholic solvent or a mixed solvent of an alcoholic solvent and water in a state where the metal-doped silica, a polymer containing a vinyl pyrrolidone unit, and an alcoholic solvent or a mixed solvent of an alcoholic solvent and water are in the desired content according to a conventional method for preparing a coating composition. The metal-doped silica, a polymer containing a vinyl pyrrolidone unit, an alcoholic solvent or a mixed solvent of an alcoholic solvent and water are preferably mixed by treating these raw materials with a ball mill. By treating metal-doped silica, a polymer containing vinyl pyrrolidone units, an alcoholic solvent or a mixed solvent of an alcoholic solvent and water with a ball mill, a coating composition can be obtained in which the metal-doped silica is uniformly dispersed without agglomeration in an alcoholic solvent or a mixed solvent of an alcoholic solvent and water in which a polymer containing vinyl pyrrolidone units is uniformly dissolved. In the formed coating film, the carried metal-doped silica is uniformly dispersed without agglomeration, thereby preventing it from falling off the coating film. Moreover, although metal-doped silica coexists at the same time, the polymer containing vinyl pyrrolidone units exerts a high adhesion to the surface of the object, and it is easy to form a coating film in which the metal-doped silica exhibits excellent antiviral properties and is firmly maintained on the surface of the object.

[0068] The ball milling treatment can be achieved by placing metal-doped silica, a polymer containing a vinyl pyrrolidone unit, an alcoholic solvent or a mixed solvent of an alcoholic solvent and water together with grinding balls (medium) used in a ball mill in a treatment container, assembling the treatment container containing these raw materials on a ball mill stand and rotating it (the number of revolutions is selected in the range of, for example, 15 to 2000 rpm). The ball milling treatment time is, for example, 1 to 50 hours, preferably 6 to 30 hours. The grinding balls used in the ball mill (for example The number of alumina balls or zirconium oxide balls) is preferably such that the weight of the grinding balls is 1 to 5 times the total weight of the dispersion medium and the solvent in which the metal-doped silica, the polymer containing vinyl pyrrolidone units, the alcoholic solvent or the mixed solvent of the alcoholic solvent and water are dissolved or dispersed, and other components are added as needed, when the metal-doped silica is provided in the form of a slurry suspended in a dispersion medium that is different from the alcoholic solvent or the mixed solvent of the alcoholic solvent and water used in the antiviral coating composition of the present invention, and the polymer containing vinyl pyrrolidone units is provided in the form of a solution dissolved in a solvent that is different from the alcoholic solvent or the mixed solvent of the alcoholic solvent and water used in the antiviral coating composition of the present invention. The alcoholic solvent or the mixed solvent of the alcoholic solvent and water contained in the processing container may be a part of the content of the antiviral coating composition of the present invention. In this case, after the ball milling treatment, the alcoholic solvent or the mixed solvent of the alcoholic solvent and water may be added to reach the content in the antiviral coating composition of the present invention.

[0069] The antiviral coating composition of the present invention can be used for fiber products, non-woven products, leather products, building materials, wood, glass, plastic, film, ceramics, paper, pulp, stationery, toys, containers, container caps, pouring tools, nozzles and other items around us for the purpose of imparting antiviral properties. The method of applying the antiviral coating composition of the present invention to the surface of an article can adopt the previously known method of applying the coating composition to the surface of an article, such as the method of filling the antiviral coating composition of the present invention with a propellant including liquefied petroleum gas, nitrogen, carbon dioxide gas, dimethyl ether, hydrofluoroolefins, hydrofluorocarbons, etc. into a spray can to form an aerosol and apply it to the surface of the article; the method of applying the antiviral coating composition of the present invention to the surface of an article using various coating devices; the method of applying the antiviral coating composition of the present invention to the surface of an article by immersing the article in the antiviral coating composition of the present invention, etc. Regardless of which method is used, by applying the antiviral coating composition of the present invention to the surface of the article and performing natural drying or heat drying, a coating film can be formed in which metal-doped silica exhibits excellent antiviral properties and is firmly maintained on the surface of the article.

[0070] In the coating formed by the antiviral coating composition of the present invention, the metal-doped silica contained in the coating not only exhibits excellent antiviral effects on enveloped viruses, but also exhibits excellent antiviral effects on non-enveloped viruses. Therefore, the type of virus as the object of the antiviral effect is not limited, and various pathogenic viruses can be used as the object. For example, as enveloped viruses, influenza A virus, influenza B virus, influenza C virus, parainfluenza virus, mumps virus (mumps virus), measles virus, human metapneumovirus, RS virus, Nipah virus, Hendra virus, yellow fever virus, dengue virus, Japanese encephalitis virus, West Nile virus, hepatitis B virus, hepatitis C virus, hepatitis D virus, Eastern equine encephalitis virus, Western equine encephalitis virus, rubella virus, Lassa virus, Junin virus, Machupo virus, South American hemorrhagic fever virus, Sabia virus, Crimean-Congo hemorrhagic fever virus, sandfly fever virus, Hanta virus, Sinnubai virus, rabies virus, The targets include Ebola virus, Marburg virus, bat lyssavirus, human T-cell leukemia virus, human immunodeficiency virus, human coronavirus, SARS coronavirus, SARS-CoV-2 virus (COVID-19 virus), herpes virus, varicella-zoster virus, Epstein-Barr virus, cytomegalovirus, smallpox virus, monkeypox virus, vaccinia virus, molluscum pox virus, parapox virus, and Ornheal virus. Non-enveloped viruses include rhinovirus, poliovirus, foot-and-mouth disease virus, rotavirus, norovirus, enterovirus, hepatovirus, astrovirus, sapovirus, hepatitis A virus, hepatitis E virus, human parvovirus, polyomavirus, human papillomavirus, adenovirus, and coxsackievirus.

[0071] In addition, the metal-doped silica contained in the antiviral coating composition of the present invention can exhibit excellent antiviral effects even during the period from the application of the antiviral coating composition of the present invention to the surface of the article until the coating film is formed. During this period, the alcohol solvent or the mixed solvent of the alcohol solvent and water contained in the antiviral coating composition of the present invention also exhibits an antiviral effect.

[0072] Example

[0073] The present invention will be described in detail below with reference to Examples, but the present invention is not to be construed as being limited to the following descriptions.

[0074] Manufacturing Reference Example 1: Manufacturing of Mesoporous Silica Doped with Copper and Aluminum

[0075] Hexadecyltrimethylammonium chloride as a surfactant, copper chloride as a raw material for doping copper into mesoporous silica, and aluminum chloride as a raw material for doping aluminum into mesoporous silica were dissolved in water as a solvent, stirred at 100°C for 1 hour, cooled to room temperature, and then tetraethoxysilane as a raw material for silica was further dissolved and stirred until uniform. Next, sodium hydroxide aqueous solution as an alkaline aqueous solution was added to the reaction solution in such a way that the pH value immediately after addition was 9, and then stirred at room temperature for 20 hours. The generated precipitate was filtered and recovered, dried at 50°C for 24 hours, and then calcined at 570°C for 5 hours, thereby obtaining the target product, mesoporous silica doped with copper and aluminum, in the form of a slightly bluish white powder.

[0076] It should be noted that the amounts of hexadecyltrimethylammonium chloride as a surfactant, copper chloride as a raw material for doping copper into mesoporous silica, aluminum chloride as a raw material for doping aluminum into mesoporous silica, and water as a solvent relative to 1 mol of tetraethoxysilane as a raw material of silica are as follows:

[0077] Hexadecyltrimethylammonium chloride: 0.225 mol

[0078] Copper chloride: 0.0204 mol

[0079] Aluminum chloride: 0.0482 mol

[0080] Water: 125 mol

[0081] In order to prepare the sodium hydroxide aqueous solution as the alkaline aqueous solution, 0.195 mol of sodium hydroxide was used per 1 mol of tetraethoxysilane as the silica raw material.

[0082] The specific surface area of ​​the mesoporous silica doped with copper and aluminum obtained by the above method is 1100 m 2 / g, the micropore diameter is about 2.5nm (using MicrotracBEL company BELSORP MAX II type, multi-point method to measure the nitrogen adsorption isotherm at liquid nitrogen temperature, calculated by BJH). In addition, about 50mg of mesoporous silica doped with copper and aluminum was accurately weighed and dissolved in 4mL of hydrochloric acid, and then the concentration of copper and aluminum in the hydrochloric acid solution was measured by inductively coupled plasma emission spectrometer (iCAP PRO XP ICP-OES made by Thermo Fisher Scientific, the same below). The copper content and aluminum content in the mesoporous silica doped with copper and aluminum were calculated based on the measurement results. The result is that the copper content is 2.09% by weight and the aluminum content is 2.00% by weight. The fact that copper and aluminum are doped in mesoporous silica can be confirmed by X-ray photoelectron spectrometer (K-Alpha Surface Analysis made by ThermoFisher Scientific, the same below) and transmission electron microscope (JEM 2010 made by JEOL, the same below).

[0083] Production Example 1: Production of the Antiviral Coating Composition of the Present Invention (Part 1)

[0084] (Process 1)

[0085] In a 2L iBoy PP wide-mouth bottle, 140 g of the mesoporous silica doped with copper and aluminum obtained in Preparation Reference Example 1, 560 g of ethanol, 1760 g of alumina balls are mounted on a ball mill stand at room temperature, treated at a rotation speed of 250 rpm for 1 hour, and then treated at a rotation speed of 450 rpm for 9 hours. The alumina balls are then removed to obtain an ethanol slurry with a median particle size of about 0.6 μm and a mesoporous silica content of 20 wt% doped with copper and aluminum (the median particle size is measured by a laser diffraction particle size distribution measuring device (SALD-3100 manufactured by Shimadzu Corporation) and the same below).

[0086] (Process 2)

[0087] 35 g of a powder of a copolymer of vinyl pyrrolidone and vinyl acetate (PVP / VA S630, manufactured by Ashland, the ratio of vinyl pyrrolidone unit to vinyl acetate unit is 6:4, weight average molecular weight (nominal value) 51,000, the same below) and 490 g of ethanol were added to a 2 L iBoy PP wide-mouth bottle. After the powder of the copolymer of vinyl pyrrolidone and vinyl acetate was dissolved in ethanol, 175 g of an ethanol slurry of mesoporous silica doped with copper and aluminum having a median particle size of about 0.6 μm and a content of 20 wt % obtained in step 1 was added. 1760g of alumina balls are assembled on a ball mill stand at room temperature and processed at a rotation speed of 500rpm for 9 hours. The alumina balls are then removed to obtain the antiviral coating composition of the present invention, which has a median particle size of about 0.5μm, a content of 5% by weight of mesoporous silica doped with copper and aluminum, a content of 5% by weight of a copolymer of vinyl pyrrolidone and vinyl acetate, and a content of 90% by weight of ethanol.

[0088] Production Example 2: Production of the Antiviral Coating Composition of the Present Invention (Part 2)

[0089] In a 2L iBoy PP wide-mouth bottle, 35 g of the mesoporous silica doped with copper and aluminum obtained in Preparation Reference Example 1, 315 g of ethanol, 350 g of a 10 wt % ethanol solution of a powder of a copolymer of vinyl pyrrolidone and vinyl acetate (PVP / VA S630), 1700g of alumina balls are assembled on a ball mill stand at room temperature and processed at a rotation speed of 900rpm for 24 hours. The alumina balls are then removed to obtain the antiviral coating composition of the present invention, which has a median particle size of about 0.5μm, a content of 5% by weight of mesoporous silica doped with copper and aluminum, a content of 5% by weight of a copolymer of vinyl pyrrolidone and vinyl acetate, and a content of 90% by weight of ethanol.

[0090] Production Example 3: Production of the Antiviral Coating Composition of the Present Invention (Part 3)

[0091] (Process 1)

[0092] In a 250 mL iBoy PP wide-mouth bottle, 4.4 g of the mesoporous silica doped with copper and aluminum obtained in Preparation Reference Example 1, 83.6 g of ethanol, 220 g of alumina balls were assembled on a ball mill stand at room temperature and processed at a rotation speed of 180 rpm for 8 hours, then the alumina balls were removed to obtain an ethanol slurry with a median particle size of about 0.5 μm and a mesoporous silica content of 5 wt% doped with copper and aluminum.

[0093] (Process 2)

[0094] The ethanol slurry with a median particle size of about 0.5 μm and a content of 5 wt% of mesoporous silica doped with copper and aluminum obtained in step 1, a powder of a copolymer of vinyl pyrrolidone and vinyl acetate (PVP / VA S630) and ethanol are mixed and stirred in a mass ratio of 20:1:79 to obtain an antiviral coating composition of the present invention having a content of 1 wt% of mesoporous silica doped with copper and aluminum with a median particle size of about 0.5 μm, a content of 1 wt% of a copolymer of vinyl pyrrolidone and vinyl acetate, and an ethanol content of 98 wt%.

[0095] Production Example 4: Production of the Antiviral Coating Composition of the Present Invention (Part 4)

[0096] The same method as in Manufacturing Example 2 is carried out, except that the 10 wt % ethanol solution of the powder of the copolymer of vinyl pyrrolidone and vinyl acetate (PVP / VA S630) is used instead of the 10 wt % ethanol solution of the powder of the copolymer of vinyl pyrrolidone and vinyl acetate (PVP / VA S630), to obtain an antiviral coating composition of the present invention having a content of 5 wt % of mesoporous silica doped with copper and aluminum and a median particle size of about 0.5 μm, a content of 2.5 wt % of the copolymer of vinyl pyrrolidone and vinyl acetate, and an ethanol content of 92.5 wt %.

[0097] Production Example 5: Production of the Antiviral Coating Composition of the Present Invention (Part 5)

[0098] The antiviral coating composition of the present invention is obtained in the same manner as in Manufacturing Example 3, except that in step 2 of Manufacturing Example 3, the ethanol slurry of the mesoporous silica doped with copper and aluminum with a median particle size of about 0.5 μm and a content of 5 wt%. The powder of the copolymer of vinyl pyrrolidone and vinyl acetate (PVP / VA S630) and ethanol are mixed in a mass ratio of 40:1:159.

[0099] Production Example 6: Production of the Antiviral Coating Composition of the Present Invention (Part 6)

[0100] In a 2L iBoy PP wide-mouth bottle, 70 g of a 50 wt% aqueous solution of a copolymer of vinyl pyrrolidone and vinyl acetate (PVP / VA W735, manufactured by Ashland, ratio of vinyl pyrrolidone unit to vinyl acetate unit is 7:3, weight average molecular weight (nominal value) 27,300), 455 g of ethanol, 175 g of an ethanol slurry of 20 wt% mesoporous silica doped with copper and aluminum having a median particle size of about 0.6 μm obtained in step 1 of Preparation Example 1, 1760g of alumina balls are assembled on a ball mill stand at room temperature and processed at a rotation speed of 500rpm for 9 hours. Then, the alumina balls are removed to obtain the antiviral coating composition of the present invention, which has a median particle size of about 0.5μm, a content of 5% by weight of mesoporous silica doped with copper and aluminum, a content of 5% by weight of a copolymer of vinyl pyrrolidone and vinyl acetate, a content of 5% by weight of water, and a content of 85% by weight of ethanol.

[0101] Production Example 7: Production of the Antiviral Coating Composition of the Present Invention (Part 7)

[0102] The same method as in Example 6 is used to obtain an antiviral coating composition of the present invention, which has a content of 5 wt % of mesoporous silica doped with copper and aluminum and a median particle size of about 0.5 μm, a content of 5 wt % of a copolymer of vinyl pyrrolidone and vinyl acetate, a content of 5 wt % of a copolymer of vinyl pyrrolidone and vinyl acetate, and a content of 90 wt % of ethanol, except that the 50 wt % aqueous solution of a copolymer of vinyl pyrrolidone and vinyl acetate (PVP / VA E335, manufactured by Ashland, Inc., a ratio of vinyl pyrrolidone units to vinyl acetate units of 5:5, and a weight-average molecular weight (nominal value) of 36,700) is used instead of the 50 wt % aqueous solution of a copolymer of vinyl pyrrolidone and vinyl acetate (PVP / VA W735).

[0103] Production Example 8: Production of the Antiviral Coating Composition of the Present Invention (Part 8)

[0104] The same method as in Example 6 is used to obtain an antiviral coating composition of the present invention, which has a content of 5 wt% mesoporous silica doped with copper and aluminum and a median particle size of about 0.5 μm, a content of 5 wt% of a copolymer of vinyl pyrrolidone and vinyl acetate, a content of 5 wt% of a copolymer of vinyl pyrrolidone and vinyl acetate, and a content of 90 wt% of ethanol, except that the 50 wt% aqueous solution of a copolymer of vinyl pyrrolidone and vinyl acetate (PVP / VA E335, manufactured by Ashland, Inc., a ratio of vinyl pyrrolidone units to vinyl acetate units of 3:7, and a weight-average molecular weight (nominal value) of 28,800) is used instead of the 50 wt% aqueous solution of a copolymer of vinyl pyrrolidone and vinyl acetate (PVP / VA W735).

[0105] Production Example 9: Production of the Antiviral Coating Composition of the Present Invention (Part 9)

[0106] The same method as in Manufacturing Example 1 was followed except that the powder of the copolymer of vinyl pyrrolidone and vinyl acetate (PVP / VA S630) was used instead of polyvinyl pyrrolidone powder (PVP K15, manufactured by Ashland, with a weight average molecular weight (nominal value) of 8,000) to obtain an antiviral coating composition of the present invention having a median particle size of about 0.5 μm, a content of 5 wt% of mesoporous silica doped with copper and aluminum, a content of 5 wt% of polyvinyl pyrrolidone, and a content of 90 wt% of ethanol.

[0107] Production Example 10: Production of the Antiviral Coating Composition of the Present Invention (Part 10)

[0108] The same method as in Manufacturing Example 1 was followed, except that the powder of the copolymer of vinyl pyrrolidone and vinyl acetate (PVP / VA S630) was replaced with polyvinyl pyrrolidone powder (PVP K30, manufactured by Ashland, with a weight average molecular weight (nominal value) of 60,000), to obtain an antiviral coating composition of the present invention having a median particle size of about 0.5 μm, a content of 5 wt% of mesoporous silica doped with copper and aluminum, a content of 5 wt% of polyvinyl pyrrolidone, and a content of 90 wt% of ethanol.

[0109] Production Example 11: Production of the Antiviral Coating Composition of the Present Invention (Part 11)

[0110] The same method as in Manufacturing Example 1 was followed except that the powder of the copolymer of vinyl pyrrolidone and vinyl acetate (PVP / VA S630) was replaced with polyvinyl pyrrolidone powder (PVP K90, manufactured by Ashland, weight average molecular weight (nominal value) 1,300,000) to obtain an antiviral coating composition of the present invention having a median particle size of about 0.5 μm, a content of 5 wt% of mesoporous silica doped with copper and aluminum, a content of 5 wt% of polyvinyl pyrrolidone, and a content of 90 wt% of ethanol. A pump sprayer filled with the antiviral coating composition of the present invention was placed horizontally, sprayed once onto a glass slide from a height of 15 cm, and then dried naturally to form a coating film on the surface of the glass slide. The coating film formed on the surface of the glass slide was white, and microscopic observation showed that the mesoporous silica carried by the coating film was uniformly dispersed without agglomeration ( Figure 1 ).

[0111] Test Example 1: Antiviral effect of the coating formed by the antiviral coating composition of the present invention on enveloped viruses

[0112] (1) Film formation by aerosol coating

[0113] The antiviral coating composition of the present invention prepared in Example 1 was mixed with ethanol in a weight ratio of 1:4 to prepare a stock solution (1% by weight of mesoporous silica doped with copper and aluminum with a median particle size of about 0.5 μm, 1% by weight of a copolymer of vinyl pyrrolidone and vinyl acetate, and 98% by weight of ethanol), and liquefied petroleum gas (vapor pressure of 0.29 MPa at 20°C, the same below) as a propellant was placed horizontally in an aerosol can filled with a weight ratio of 6:4, and evenly sprayed from a height of 15 cm to the entire surface of a 10 cm×20 cm PET film for 7 seconds (spraying amount 1.36 g / sec) and then dried naturally to form a coating film on the surface of the PET film. Moreover, when the aerosol composition was sprayed from the aerosol can, no spray failure caused by nozzle clogging was observed. The coating film formed on the surface of the PET film was white, and the carrying capacity of mesoporous silica doped with copper and aluminum with a median particle size of about 0.5 μm was 0.27 mg / cm 2It should be noted that the carrying capacity of mesoporous silica is calculated based on the amount of copper in the crucible measured by an inductively coupled plasma emission spectrometer after a PET film with a white coating formed on the surface is placed in a crucible and 6 mol / L hydrochloric acid is added and heated at 120°C for 1 hour.

[0114] (2) Evaluation of antiviral effects

[0115] MDCK cells (canine kidney-derived cells) as host cells were infected with influenza A virus (H3N2, A / Hong Kong / 8 / 68; TC adaptability, ATCC VR-1679), and the cell residues were removed by centrifugation after culture to obtain a virus suspension (infectious titer: 4.7×10 7 PFU / mL). According to ISO 21702, 0.4 mL of the virus suspension was dripped onto a 5 cm square test piece cut from a PET film with a white coating formed on the surface, covered with a 4 cm square covering film, and allowed to stand at 25°C. After 24 hours, a virus washing solution was applied to the test piece to wash away the virus, and the virus infection titer was measured by a plaque assay. The results are shown in Table 1. It should be noted that Table 1 also shows the results of the same test using the antiviral coating composition of the present invention prepared in Manufacturing Examples 6 to 8, as well as the results when the virus suspension was dripped onto a 5 cm square PET film as a control.

[0116] [Table 1]

[0117]

[0118] PVP / VA: copolymer of vinyl pyrrolidone and vinyl acetate

[0119] VP:VA: ratio of vinyl pyrrolidone units to vinyl acetate units

[0120] Mw: weight average molecular weight (nominal value)

[0121] Antiviral activity value [R] = [U t ]-[A t ]

[0122] As shown in Table 1, the coating films formed by the antiviral coating compositions of the present invention prepared in Production Examples 1 and 6 to 8 exhibited excellent antiviral effects on influenza viruses, which are enveloped viruses.

[0123] Test Example 2: Antiviral effect of the coating formed by the antiviral coating composition of the present invention on non-enveloped viruses

[0124] (1) Formation of coating film by aerosol coating

[0125] The antiviral coating composition of the present invention prepared in Preparation Example 1 was subjected to the same test as in Test Example 1 to form a white coating film on the surface of a 10 cm×20 cm PET film.

[0126] (2) Evaluation of antiviral effects

[0127] CRFK cells (feline kidney-derived cells) as host cells were infected with feline calicivirus (F-9, strain: F-9, ATCC VR-782), which was used as a substitute virus for norovirus. After culture, cell debris was removed by centrifugation to obtain a virus suspension (infectious titer: 2.4×10 7 PFU / mL). According to ISO 21702, 0.4 mL of the virus suspension was dripped onto a 5 cm square test piece cut from a PET film with a white coating formed on the surface, covered with a 4 cm square covering film, and allowed to stand at 25°C. After 24 hours, a virus washing solution was applied to the test piece to wash away the virus, and the virus infection titer was measured by a plaque assay. The results are shown in Table 2. It should be noted that Table 2 also shows the results of the same test using the antiviral coating composition of the present invention prepared in Manufacturing Examples 6 to 8, as well as the results when the virus suspension was dripped onto a 5 cm square PET film as a control.

[0128] [Table 2]

[0129]

[0130] PVP / VA: copolymer of vinyl pyrrolidone and vinyl acetate

[0131] VP:VA: ratio of vinyl pyrrolidone units to vinyl acetate units

[0132] Mw: weight average molecular weight (nominal value)

[0133] Antiviral activity value [R] = [U t ]-[A t ]

[0134] As shown in Table 2, the coating films formed by the antiviral coating compositions of the present invention prepared in Production Examples 1 and 6 to 8 exhibited excellent antiviral effects on feline calicivirus, which is a non-enveloped virus.

[0135] Test Example 3: Adsorption of hemagglutinin (HA) by the coating formed by the antiviral coating composition of the present invention

[0136] The adsorption of HA, a surface protein of influenza virus, on the coating film formed by the antiviral coating composition of the present invention was evaluated using the HA (H1N1) (A / California / 06 / 2009 hemagglutinin ELISA development kit (Immune Technology IT-E3Ag-2009H1N1-California / 06). Specifically, the antiviral coating composition of the present invention prepared in Preparation Example 1 was used in the same manner as in Test Example 1. A PET film having a white coating film of 10 cm×20 cm on the surface was cut out to obtain an area of ​​7.4 cm 2 The test piece (2 mg of mesoporous silica doped with copper and aluminum with a median particle size of about 0.5 μm) was immersed in 2 mL of HA solution with an initial concentration of 25.3 ng / mL, stirred for 20 seconds using a vortex mixer, and allowed to stand at room temperature. After 3 minutes, the film was removed, and then centrifuged to settle the solid components. The supernatant was collected and its HA concentration was measured. The adsorption rate relative to HA was calculated according to the formula: Adsorption rate (%) = ((HA initial concentration - HA concentration after 3 minutes) / HA initial concentration) × 100. 2 mg of mesoporous silica doped with copper and aluminum with a median particle size of about 0.5 μm was added to 2 mL of HA solution with an initial concentration of 25.3 ng / mL. When the adsorption rate of mesoporous silica for HA calculated based on the same method as above was taken as 100, the relative values ​​of the adsorption rate for HA calculated in the test example are shown in Table 3. It should be noted that Table 3 also shows the results of the same test using the antiviral coating compositions of the present invention prepared in Preparation Examples 9 to 11.

[0137] [Table 3]

[0138]

[0139] PVP / VA: copolymer of vinyl pyrrolidone and vinyl acetate

[0140] VP:VA: ratio of vinyl pyrrolidone units to vinyl acetate units

[0141] PVP: Polyvinylpyrrolidone

[0142] Mw: weight average molecular weight (nominal value)

[0143] It can be seen from Table 3 that the adsorption rate of the coating formed by the antiviral coating composition of the present invention prepared in Example 1 relative to HA is almost the same as the adsorption rate of mesoporous silica doped with copper and aluminum with a median particle size of about 0.5 μm for HA, and the coexistence of the copolymer of vinyl pyrrolidone and vinyl acetate in the coating almost does not lead to a decrease in the adsorption rate of mesoporous silica for HA. Therefore, it can be confirmed that the coating formed by the antiviral coating composition of the present invention prepared in Example 1 has an excellent adsorption effect on HA. The adsorption rate of the coating formed by the antiviral coating composition of the present invention prepared in Examples 9 to 11 for HA decreases as the weight average molecular weight of polyvinyl pyrrolidone increases. From this result, it can be inferred that if the weight average molecular weight of the polymer containing the vinyl pyrrolidone unit is too large, it is possible to inhibit the expression of the antiviral properties of the mesoporous silica contained in the formed coating.

[0144] Test Example 4: Durability of the coating film formed by the antiviral coating composition of the present invention (coated by aerosol)

[0145] Similar to Test Example 1, the stock solution prepared from the antiviral coating composition of the present invention prepared in Manufacturing Example 1 (1% by weight of mesoporous silica doped with copper and aluminum with a median particle size of about 0.5 μm, 1% by weight of a copolymer of vinyl pyrrolidone and vinyl acetate, and 98% by weight of ethanol) and a liquefied petroleum gas as a propellant filled in a 6:4 weight ratio were placed horizontally in an aerosol can, sprayed from a height of 15 cm onto a PET film for 1 second and dried naturally. Two test pieces (Test piece A and Test piece B) of 2 cm×4 cm were cut out from the PET film with a white coating of about 6 cm in diameter formed on the surface. Press the entire surface of the coating of Test piece A by hand. (Registered trademark, the same below) The tape is peeled off immediately after being firmly attached. The tape-covered test pieces A and B were placed in crucibles, 6 mol / L hydrochloric acid was added and heated at 120°C for 1 hour. The amount of copper in the crucible was measured using an inductively coupled plasma emission spectrometer, and the results were respectively The copper content of test piece A and test piece B after the tape is peeled off. The durability of the coating film was evaluated by using a numerical formula. The results are shown in Table 4. It should be noted that Table 4 also shows the results of the same test on the antiviral coating composition (stock solution) of the present invention prepared in Example 5 (the content of mesoporous silica doped with copper and aluminum with a median particle size of about 0.5 μm is 1 weight%, the content of a copolymer of vinyl pyrrolidone and vinyl acetate is 0.5 weight%, and the content of ethanol is 98.5 weight%) and liquefied petroleum gas as a propellant filled into an aerosol can at a weight ratio of 6:4; the stock solution prepared from the antiviral coating composition of the present invention prepared in Example 6 (the content of mesoporous silica doped with copper and aluminum with a median particle size of about 0.5 μm is 1 weight%, the content of a copolymer of vinyl pyrrolidone and vinyl acetate is 0.5 weight%, and the content of ethanol is 98.5 weight%). The results of the same test are as follows: an aerosol can containing 1 wt% aluminum mesoporous silica, 1 wt% copolymer of vinyl pyrrolidone and vinyl acetate, 1 wt% water and 97 wt% ethanol, and liquefied petroleum gas as a propellant at a weight ratio of 6:4, and a control solution containing 1 wt% mesoporous silica doped with copper and aluminum, 99 wt% ethanol, and liquefied petroleum gas as a propellant at a weight ratio of 6:4, and aerosol cans were filled with the same test results.

[0146] [Table 4]

[0147]

[0148] PVP / VA: copolymer of vinyl pyrrolidone and vinyl acetate

[0149] VP:VA: ratio of vinyl pyrrolidone units to vinyl acetate units

[0150] Mw: weight average molecular weight (nominal value)

[0151] As shown in Table 4, by using a polymer containing a vinyl pyrrolidone unit as the resin component of the coating composition, a coating film that can be firmly maintained can be formed on the surface of the PET film by aerosol coating.

[0152] Test Example 5 Durability of the coating film formed by the antiviral coating composition of the present invention (coating by coating device)

[0153] The antiviral coating composition of the present invention prepared in Example 1 was applied to the surface of the PET film using a rod coater #10 and dried naturally. Two test pieces (test piece C and test piece D) with a 5 cm square were cut out from the PET film with a white coating film of about 1.4 μm thick formed on the surface. The entire surface of the coating film of test piece C was pressed by hand. Once the tape is firmly attached, peel it off immediately. The tape-covered test pieces C and D were placed in crucibles, 6 mol / L hydrochloric acid was added and heated at 120°C for 1 hour. The copper content in the crucible was measured using an inductively coupled plasma emission spectrometer to obtain the following results: The copper content of test pieces C and D after the tape is peeled off. The durability of the coating film was evaluated by using the formula of . The results are shown in Table 5. It should be noted that Table 5 also shows the results of the same test using the antiviral coating composition of the present invention prepared in Manufacturing Examples 4, 6 to 8, and the results of the same test using a coating composition as a control product, which was coated on the surface of a PET film using a coating device and contained 5% by weight of mesoporous silica doped with copper and aluminum and 95% by weight of ethanol.

[0154] [Table 5]

[0155]

[0156] PVP / VA: copolymer of vinyl pyrrolidone and vinyl acetate

[0157] VP:VA: ratio of vinyl pyrrolidone units to vinyl acetate units

[0158] Mw: weight average molecular weight (nominal value)

[0159] As shown in Table 5, by using a polymer containing a vinyl pyrrolidone unit as the resin component of the coating composition, a coating film that can be firmly maintained can be formed on the surface of the PET film by coating with an applicator.

[0160] Manufacturing Reference Example 2: Manufacturing of Mesoporous Silica Doped with Aluminum

[0161] The same method as in Preparation Reference Example 1 was used except that the copper chloride used as a raw material for doping copper into mesoporous silica in Preparation Reference Example 1 was not used to obtain white powder of aluminum-doped mesoporous silica (specific surface area: 1151 m 2 / g, micropore diameter: 2.5 nm, aluminum content: 1.82 wt%).

[0162] Production Example 12: Production of the Antiviral Coating Composition of the Present Invention (Part 12)

[0163] The same method as in Manufacturing Example 1 was used except that the mesoporous silica doped with aluminum obtained in Manufacturing Reference Example 2 was used instead of the mesoporous silica doped with copper and aluminum obtained in Manufacturing Reference Example 1, thereby obtaining an antiviral coating composition of the present invention having a content of 5% by weight of mesoporous silica doped with aluminum having a median particle size of about 0.5 μm, a content of a copolymer of vinyl pyrrolidone and vinyl acetate of 5% by weight, and an ethanol content of 90% by weight. The coating film formed by the antiviral coating composition of the present invention has the same antiviral effect and durability as the coating film formed by the antiviral coating composition of the present invention prepared in Manufacturing Example 1.

[0164] Manufacturing Reference Example 3: Manufacturing of Non-porous Silica Doped with Copper and Aluminum

[0165] A solution (a) formed by dissolving sodium silicate (sodium metasilicate (nonahydrated salt): manufactured by Nippon Chemical Industry Co., Ltd., SiO2 / Na2O=0.9-1.1 (manufacturer's nominal value)) as a raw material for silica in water as a solvent, and a solution (b) formed by dissolving copper chloride as a raw material for doping copper into non-porous silica and aluminum chloride as a raw material for doping aluminum into non-porous silica in water as a solvent were prepared separately. After mixing and stirring the solution (a) and the solution (b) at room temperature for 5 minutes, hydrochloric acid was further added dropwise for 30 minutes under stirring (the pH value at the beginning of the addition of hydrochloric acid was 14, and the pH value at the end was 9). After about 30 minutes, the generated precipitate was filtered by suction, and the filtered precipitate was thoroughly washed with water (until the conductivity of the washing liquid was less than 1000μS), and then dried at 80°C overnight. The recovered filter cake was roughly ground with a mixer and then fired at 570° C. for 5 hours, thereby obtaining the target product, non-porous silica doped with copper and aluminum, as a slightly bluish white powder.

[0166] It should be noted that the amounts of copper chloride as a raw material for doping copper into non-porous silica, aluminum chloride as a raw material for doping aluminum into non-porous silica, and water as a solvent relative to 1 mol of sodium silicate as a raw material for silica are as follows:

[0167] Copper chloride: 0.0201 mol

[0168] Aluminum chloride: 0.0475 mol

[0169] Solution (a) Preparation Water: 48.6 mol

[0170] Solution (b) Preparation Water: 90.2 mol

[0171] Furthermore, 1.59 mol of hydrochloric acid was used per 1 mol of sodium silicate as a raw material of silica.

[0172] The BET specific surface area of ​​the non-porous silica doped with copper and aluminum obtained by the above method is 18.8 m 2 / g. In addition, the copper content in the non-porous silica doped with copper and aluminum was 1.43 wt%, and the aluminum content was 2.03 wt%. The doping of copper and aluminum in the non-porous silica was confirmed by X-ray photoelectron spectroscopy and transmission electron microscopy.

[0173] Production Example 13: Production of the Antiviral Coating Composition of the Present Invention (Part 13)

[0174] The same method as in Manufacturing Example 1 was used except that the mesoporous silica doped with copper and aluminum obtained in Manufacturing Reference Example 1 was used instead of the non-porous silica doped with copper and aluminum obtained in Manufacturing Reference Example 3, thereby obtaining an antiviral coating composition of the present invention having a non-porous silica doped with copper and aluminum with a median particle size of about 0.5 μm, a content of 5% by weight of a copolymer of vinyl pyrrolidone and vinyl acetate, and a content of 90% by weight of ethanol. The coating film formed by the antiviral coating composition of the present invention has the same antiviral effect and durability as the coating film formed by the antiviral coating composition of the present invention prepared in Manufacturing Example 1.

[0175] Industrial Applicability

[0176] The present invention has industrial applicability because it can provide an antiviral coating composition that can form a coating film that exhibits excellent antiviral performance of metal-doped silica and is firmly maintained on the surface of an article, a coating film formed by the antiviral coating composition, and an article having the coating film.

Claims

1. An antiviral coating composition, It is characterized in that contain: (1) Metal-doped silica; (2) polymers containing vinyl pyrrolidone units; and (3) An alcohol solvent or a mixed solvent of an alcohol solvent and water.

2. The antiviral coating composition according to claim 1, It is characterized in that The metal doped into silicon dioxide is selected from at least one of copper, aluminum, zirconium, cobalt, manganese and iron.

3. The antiviral coating composition according to claim 2, It is characterized in that The metals doped into the silicon dioxide are copper and / or aluminum.

4. The antiviral coating composition according to claim 1, It is characterized in that The silicon dioxide is porous silicon dioxide.

5. The antiviral coating composition according to claim 1, It is characterized in that The polymer containing a pyrrolidone unit is a copolymer of a vinyl pyrrolidone unit and a unit other than vinyl pyrrolidone.

6. The antiviral coating composition according to claim 5, It is characterized in that The ratio of the vinyl pyrrolidone unit to the unit other than vinyl pyrrolidone is 2:8 to 8:2 in terms of vinyl pyrrolidone unit:unit other than vinyl pyrrolidone.

7. The antiviral coating composition according to claim 5, It is characterized in that The copolymer of a vinyl pyrrolidone unit and a unit other than vinyl pyrrolidone is a copolymer of vinyl pyrrolidone and vinyl acetate.

8. The antiviral coating composition according to claim 1, It is characterized in that The polymer containing pyrrolidone units is polyvinylpyrrolidone.

9. The antiviral coating composition according to claim 1, It is characterized in that The weight average molecular weight of the polymer containing the pyrrolidone unit is 5,000 to 1,500,000.

10. The antiviral coating composition according to claim 1, It is characterized in that The alcohol solvent is ethanol.

11. The antiviral coating composition according to claim 1, It is characterized in that The contents of metal-doped silica, polymer containing vinyl pyrrolidone units, alcohol solvent or mixed solvent of alcohol solvent and water in the antiviral coating composition are: the content of metal-doped silica is 0.1 to 20 weight %, the content of polymer containing vinyl pyrrolidone units is 0.1 to 20 weight %, and the content of alcohol solvent or mixed solvent of alcohol solvent and water is 60 to 99.8 weight %.

12. The antiviral coating composition according to claim 1, It is characterized in that The weight ratio of the metal-doped silica to the polymer containing the vinyl pyrrolidone unit is 1:99 to 75:25 in terms of metal-doped silica:polymer containing the vinyl pyrrolidone unit.

13. A method for producing an antiviral coating composition, It is characterized in that include: The following (1) to (3) are placed in a processing container and subjected to ball milling treatment. (1) Metal-doped silica; (2) polymers containing vinyl pyrrolidone units; and (3) An alcohol solvent or a mixed solvent of an alcohol solvent and water.

14. An antiviral coating, It is characterized in that The invention comprises (1) metal-doped silica and (2) a polymer containing vinyl pyrrolidone units.

15. The antiviral coating according to claim 14, It is characterized in that The antiviral coating film is formed from the antiviral coating composition according to claim 1.

16. An item, It is characterized in that An antiviral coating according to claim 14.

Citation Information

Patent Citations

  • Porous silica, deodorant, and method for producing deodorant

    JP2020015640A

  • Anti-fog coating composition, anti-fog thin film and product

    CN101747690A

  • Coating composition for antireflection coating and preparation method thereof as well as antireflection film prepared from coating composition

    CN107011760A

  • Antibacterial coating, antibacterial coating manufacturing method, antibacterial coating and antiviral adhesive tape

    CN113667406A

  • NEW ANTIMICROBIAL AGENT BASED ON DOPED SILICON OXIDE PARTICLES

    FR3085104A1